Asphalt Thermos Sdn. Bhd. / Irwan Faiz Ruslan ... [et al.] - Ruslan, Irwan Faiz; Ibrahim, Mohd Hafizul; Said, Muhd Nusser; Muharin, Mohd Al-Helmi (Faculty of Architecture, Planning and Surveying, 2005)
The marketing activity is defined as the process of planning and executing the conception, pricing, promotions and distribution of ideas, goods and services to create exchanges that satisfy individual and organizational objectives. Marketing activities that are carried out systematically to encourage and increase sales of products/services as long as the activities are in line with religious and ethical practices. Marketing also is a social and managerial process by which individuals and groups obtain what they need and what through creating and exchanging products and value with others. In conformity with the customers satisfaction there is several efforts can be using by company depends on themselves to proceed it as long as it not differ from our religion and human ethics.